Comparison of conventional fixed learning module with computerised fixed learning module in teaching md phase ii students - Madhavan, Manoharan; Kaur, Gurjeet (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: Fixed Learning Module (FLM) is one of the important teaching methods for undergraduate medical students within the integrated system. The resource material of pathology is conventionally exhibited as potted specimens and charts. In this conventional FLM ( conFLM), the students find difficulty in understanding pathology due to various reasons. Aim: To create an alternate FLM- computerized FLM ( comFLM)- material using a web based, interactive computer technology and to compare its effectiveness with the conFLM. Materials & Methods: The conFLM materials were selected from the pathology museum. The comFLM (an HTh1L program) was prepared on female reproductive block (FRB) and musculoskeletal block (MSB) using digital photographs of potted specimens and java script and uploaded in the USM intranet. The phase II 1\ID students were divided into two groups. Each group was exposed to only one type of FLM for each block with a cross over. At the end of each block, the students were given a questionnaire and also assessed by MCQ, computerized objective structured clinical examination (OSCE) and conventional OSCE examination. The data were collected and analysed by Mann Whitney test. Result: Significant difference was observed only in MCQ marks in MSB and computerized OSCE marks in FRB. More than 60% of the students felt comFLM was more interesting, user friendly and they could attend more than once and could learn in their own pace. In contrast, majority ( 61%) of the students faced problem in conFLM and were unable to appreciate the pathological features seen in the specimen. Conclusion: The computerized FLM had many advantages. However it might not replace the conventional FLM and indeed, both appear complementary to each other in effective learning of pathology FLM.